2014
DOI: 10.1007/s11002-014-9279-0
|View full text |Cite
|
Sign up to set email alerts
|

Are look-alikes confusing? The application of the DRM paradigm to test consumer confusion in counterfeit cases

Abstract: The Deese-Roediger-McDermott (DRM) paradigm was used to investigate consumer confusion between original and look-alike brands. The results showed that look-alike brands were falsely recognized at a higher rate than original brands and that modality (audio, visual, and audiovisual) had no effect on false recognition rates. The results suggest that the DRM paradigm provides a useful tool for analyzing consumer confusion, brand substitution, and trademark infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Counterfeit goods are a common sight in many Asian markets and countless consumers are often duped into buying fake goods due to their inability to distinguish fake products from genuine ones (Clear, 2013; Falkowski et al , 2015; MarkMonitor Research, 2015). Recent research has demonstrated that consumers’ ability to recognize and recall the details of a brand logo (even of well established brands e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Counterfeit goods are a common sight in many Asian markets and countless consumers are often duped into buying fake goods due to their inability to distinguish fake products from genuine ones (Clear, 2013; Falkowski et al , 2015; MarkMonitor Research, 2015). Recent research has demonstrated that consumers’ ability to recognize and recall the details of a brand logo (even of well established brands e.g.…”
mentioning
confidence: 99%
“…In this paper, we add to the literature on counterfeiting by examining the ability of consumers to discriminate real brand logos from counterfeits at different levels of visual and semantic similarity. The rationale behind our interest is that although some consumers actively seek out counterfeit products, many others who are looking to purchase the genuine article, are often deceived into purchasing fakes due to the similarity of the counterfeit products’ logo with that of the original brand (Falkowski et al , 2015). Here, we investigate whether and to what extent consumers can recognize differences between real and fake logotypes[1] both explicitly (i.e.…”
mentioning
confidence: 99%
“…The concept of information similarity as an antecedent of confusion started with the similarity and imitation issues faced by consumers because of lookalike brands. Imitator brands often imitate market leader brands along marketing mix elements such as origin/source, colour, shape, packaging and design (Kapferer, 1995;Foxman et al, 1990;Falkowski et al, 2015). These practices lead to consumer brand confusion, misinterpretation of brand identity, hampering of the brand image of the original brand and even switching of preferences of the consumer from original to imitator brand (Foxman et al, 1990).…”
Section: Informational Factorsmentioning
confidence: 99%
“…In addition, there are two types of lookalikes in the marketplacedeceptive and non-deceptive (OECD, 2007). In the deceptive (primary) market, consists primarily from counterfeit products and unscrupulous manufacturers or retailers cheat the customers by selling counterfeits of well-known brands without the customers" knowledge (Falkowski et al, 2014;Grossman and Shapiro, 1988). In non-deceptive (secondary) market, consumers knowingly and deliberately buy lookalike products, such as personal accessories, pirated music CDs, movie DVDs or software (Wang, et al, 2005;Penz, Schlegelmilch and Stöttinger, 2009;Penz and Stöttinger, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The contemporary view understands brands as holders of the identity and meanings that are co-created in a stakeholder network (Brodie et al , 2017) and manufacturing firms are only the owners of the trademark (Evans et al , 2019). Recent research explored the equity of luxury brands (Nia and Zaichkowsky, 2000), consumer perceived risk (Veloutsou and Bian, 2008), counterfeit ownership (Bian and Moutinho, 2011), customer confusion (Falkowski, Olszewska and Ulatowska, 2014), the spotlight effect (Zhan et al , 2015), purchase intention (Le Roux et al , 2019) and conceptualizations of collaborative processes (Evans et al , 2019). Copycats are products that have a different brand name but look very similar to an existing brand and therefore they confuse consumers (Coelho do Vale and Verga Matos, 2015; Le Roux et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%